Caregiver Emotional Burden in Testicular Cancer Patients: From Patient to Caregiver Support - De Padova, Silvia; Casadei, Chiara; Berardi, Alejandra; Bertelli, Tatiana; Filograna, Alessia; Cursano, Maria Concetta; Menna, Cecilia; Burgio, Salvatore Luca; Altavilla, Amelia; Schepisi, Giuseppe; Prati, Sabrina; Montalti, Sandra; et al. (Frontiers in Endocrinology, 2019)
Testicular cancer is the most common tumor in young males aged 15-40 years. The overall cure rate for men with testicular cancer is >90%, so a huge number of these patients will become testicular cancer survivors. These people may feel some stress in the experience of diagnosis, treatment, consequences that affect the quality of life and during follow-up, especially when new issues and emotional distresses appear over time, such as late side-effects of treatments and emotional challenges including fear of tumor relapse, fertility and sexuality concerns, and social and workplace issues. The cancer experience has an impact not only on patients, but also on their relatives (e.g. spouses, parents, or siblings), who often had to assume a caregiving role for the duration of and after treatment surviving the challenges of cancer. Moreover, the caregiver plays an important role in supporting a man with a testicular cancer, providing physical and emotional care. This review presents a summary of existing knowledge regarding the impact and the burden of testicular cancer on caregiver.